'An ethnographical laboratory': science, religion and the origins of the North-West Reserve. Issue 2 (3rd April 2019) - Foster, Robert
Abstract: South Australia's 'North-West Reserve', the core of what is now Pitjantjatjara Lands, was established in 1921. It is significant for being one of the first Aboriginal reserves established specifically to protect Aboriginal people from forced cultural change. This article examines the campaign to have the reserve proclaimed, which commenced in 1914, and the subsequent contest over its management through to the establishment of Ernabella mission on its eastern boundary in 1937. It focuses especially on how scientific ideas of race began to challenge established religious approaches to the management of Aboriginal reserves.